Why some women fail to give birth at health facilities: A comparative study between Ethiopia and Nigeria - Yaya, Sanni (PLoS One, 2018)
BACKGROUND: Obstetric complications and maternal deaths can be prevented through safe delivery process. Facility based delivery significantly reduces maternal mortality by increasing women’s access to skilled personnel attendance. However, in sub-Saharan Africa, most deliveries take place without skilled attendants and outside health facilities. Utilization of facility-based delivery is affected by socio-cultural norms and several other factors including cost, long distance, accessibility and availability of quality services. This study examined country-level variations of the self-reported causes of not choosing to deliver at a health facility. METHODS: Cross-sectional data on 37,086 community dwelling women aged between 15–49 years were collected from DHS surveys in Ethiopia (n = 13,053) and Nigeria (n = 24,033). Outcome variables were the self-reported causes of not delivering at health facilities which were regressed against selected sociodemographic and community level determinants. In total eight items complaints were identified for non-use of facility delivery: 1) Cost too much 2) Facility not open, 3) Too far/no transport, 4) don’t trust facility/poor service, 5) No female provider, 6) Husband/family didn’t allow, 7) Not necessary, 8) Not customary. Multivariable regression methods were used for measuring the associations. RESULTS: In both countries a large proportion of the women mentioned facility delivery as not necessary, 54.9% (52.3–57.9) in Nigeria and 45.4% (42.0–47.5) in Ethiopia. Significant urban-rural variations were observed in the prevalence of the self-reported causes of non-utilisation. Women in the rural areas are more likely to report delivering at health facility as not customary/not necessary and healthy facility too far/no transport. However, urban women were more likely to complain that husband/family did not allow and that the costs were too high. CONCLUSION: Women in the rural were more likely to regard facility delivery as unnecessary and complain about transportation and financial difficulties. In order to achieving the maternal mortality related targets, addressing regional disparities in accessing maternal healthcare services should be regarded as a priority of health promotion programs in Nigeria and Ethiopia.